Comparative analysis on Chinese and foreign innovation performance research—based on Bibliometrics and science mapping analysis. Issue 2 (23rd November 2019) - Fang, Xiaochen; Zhu, Jinwei
Abstract : Purpose: This paper aims to present a systematic review of the literature concerning major aspects of innovation performance and compare the research hotspots of innovation performance in the twenty-first century with three primary purposes: first, to view the trend of Chinese and English literature on innovation performance research; second, to summarize the research streams in innovation performance; and third, to predict possible directions for future innovation performance research. Design/methodology/approach: The authors first introduce a framework of innovation performance research developments. Then they construct a representative data set of bibliographic records, obtaining 1, 768 articles in the SSCI citation index database and 1, 431 articles in the CSSCI database. The authors then make a comparative analysis from two aspects: research themes and development of academic communities. The research objects are keywords and references so that co-word and co-cited reference networks are established. Finally, the authors combine the direction of research streams about "innovation performance" to summarize 28 questions in three research fields that can be studied in the future. Findings: The momentum of the literature in English on innovation performance is increasing, whereas the Chinese literature has declined in recent years. The direction of research streams in Chinese and English literature is the same: they are the "innovation system/elements" research stream, the "innovation activity/ability" research stream and the "innovation network/social capital" research stream. Although the directions are the same, the specific contents of the research are different. The direction of future development of innovation performance research can be undertaken in three aspects: follow research into expanding hot topics, mine the research of typical academic circles and develop research into exploring more fields. Combined with the direction of research streams, 28 questions in three research fields are summarized. Originality/value: Based on the background of "mass entrepreneurship and innovation" in China, the research on enterprise "innovation performance" is becoming more and more important. The findings help us summarize the research streams related to innovation performance research, better understand the themes that point to directions for future development of innovation performance research and summarize 28 questions.